Eksplorasi Tingkat Empati Siswa Sekolah Islam - Nining Maizura; Alief Laili Budiyono; Khairul Bariyyah (Jurnal Psikoedukasi dan Konseling, 2025)
Empathy is a key ability that enables individuals to understand and feel the conditions of others, playing a significant role in the moral development of adolescents. Given the numerous challenges faced by adolescents due to low empathy skills, this study aims to measure the level of empathy among junior high school students. Utilizing a descriptive quantitative method, the findings indicate that 71% (22 students) exhibit a high level of empathy, while 26% (8 students) fall into the very high category, reflecting profound understanding and sensitivity toward their surroundings. Only 3% (1 student) was categorized as having low empathy. These results affirm that students of SMP Islam Diponegoro Wagir generally possess excellent empathy levels, reflecting a culture of mutual respect and strong social sensitivity. The study recommends the development of empathy training programs, such as role-playing and group discussions, to further enhance empathy awareness and skills among students